Is there a link between mesh implantation and systematic autoimmune disease? - Junsheng Li; Xiangyu Shao; Tao Cheng; Zhenling Ji (International Journal of Abdominal Wall and Hernia Surgery, 2022)
Autoimmune/autoinflammatory syndrome induced by adjuvants (ASIA)/“Shoenfeld’s syndrome” corresponds to a spectrum of immune-mediated diseases triggered by exposure to various materials. Polypropylene (PP) mesh has become the standard for nearly all kinds of hernia repair. There are conflicting reports on the link between ASIA and PP mesh implantation for hernia repair. We reported a typical ASIA/“Shoenfeld’s syndrome” after inguinal hernia repair with PP mesh, and the patient′s systematic syndrome was completely alleviated after mesh removal. The present case highlights that there is a link between ASIA/“Shoenfeld’s syndrome” and hernia repair with PP mesh, although not frequently. Both surgeons and patients should bear in mind this disease, and patients should be fully informed before surgery, and registry is an important and possible tool to evaluate and determine the frequency of ASIA after hernia repairs with PP meshes.